2014
DOI: 10.1111/nph.13068
|View full text |Cite
|
Sign up to set email alerts
|

Community assembly of ectomycorrhizal fungi along a subtropical secondary forest succession

Abstract: SummaryEnvironmental selection and dispersal limitation are two of the primary processes structuring biotic communities in ecosystems, but little is known about these processes in shaping soil microbial communities during secondary forest succession.We examined the communities of ectomycorrhizal (EM) fungi in young, intermediate and old forests in a Chinese subtropical ecosystem, using 454 pyrosequencing.The EM fungal community consisted of 393 operational taxonomic units (OTUs), belonging to 21 EM fungal line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
75
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(85 citation statements)
references
References 74 publications
8
75
0
2
Order By: Relevance
“…This observation implies that older forests with little disturbance due to the absence of silvicultural measures foster more similar mycorrhizal communities. In agreement with other studies (Gao et al., ; Peay, Garbelotto, & Bruns, ; Peay, Kennedy, & Talbot, ; Peay, Schubert, Nguyen, & Bruns, ), dispersal limitations might have been prevalent in the unmanaged forests of our study. As a result, patches with high within‐community similarities could evolve.…”
Section: Discussionsupporting
confidence: 94%
“…This observation implies that older forests with little disturbance due to the absence of silvicultural measures foster more similar mycorrhizal communities. In agreement with other studies (Gao et al., ; Peay, Garbelotto, & Bruns, ; Peay, Kennedy, & Talbot, ; Peay, Schubert, Nguyen, & Bruns, ), dispersal limitations might have been prevalent in the unmanaged forests of our study. As a result, patches with high within‐community similarities could evolve.…”
Section: Discussionsupporting
confidence: 94%
“…For example, a total of 66 and 26 EM fungal taxa were found from roots of Quercus liaotungensis and Pinus tabulaeformis in a temperate forest ecosystem using direct internal transcribed spacer (ITS) sequencing of EM root tips (Wang and Guo 2010; Wang et al 2012). By using 454 pyrosequencing, an average of 37.8 AM fungi was obtained from each of 17 woody plant species (Chen et al 2017), and an average of 32.8 EM fungi was found in each of 12 mixed root samples (Gao et al 2015) in a subtropical forest. In the agro-ecosystems, there were average 10−16 and 22−27 AM fungi observed in maize or rice root and soil samples, by using terminal restriction fragment length polymorphism and/or clone library analyses (Liu et al 2014, 2016; Wang et al 2015), but an average 29−49 AM fungi was detected in soil samples by using 454 pyrosequencing technique (Lin et al 2012).…”
Section: Mycorrhizal Fungal Diversitymentioning
confidence: 99%
“…The EM fungal community composition was significantly different in young forest (<40 years) from intermedium (41−80 years) and old (>80 years) forests, and the EM fungal community assembly was significantly structured by environmental selection in the young and intermedium forests, but by environmental selection and dispersal limitation in the old forest in a subtropical ecosystem (Gao et al 2015). Further study in this subtropical forest ecosystem showed that EM fungal composition was significantly affected by plant species composition and geographic distance in the ridge habitat but by soil pH in the valley habitat; in contrast, AM fungal community composition was not significantly influenced by any variables investigated in the ridge and valley habitats (Gao et al 2017).…”
Section: Mycorrhizal Fungal Communitymentioning
confidence: 99%
“…Guzmán, 1970. Brundrett et al, 1996 corrhizal fungi (Gao et al, 2015). These tools, besides allowing the identification of ectomycorrhizae, can contribute to a better understanding of the mutualistic interaction between plant and fungus (Larsen et al, 2011;Sebastiana et al, 2014).…”
Section: Molecular Techniquesmentioning
confidence: 99%